2014
DOI: 10.1002/clc.22336
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Analysis of Myeloperoxidase for Prediction of Adverse Events After Suspected Acute Coronary Ischemia

Abstract: Background: Myeloperoxidase (MPO) plasma values predict major adverse cardiac events (MACE) in cases of acute coronary syndrome. The effect of serial testing in patients who are suspected for acute coronary ischemia is unclear. Hypothesis: We hypothesize that sequential MPO measurement may improve prediction of MACE in patients with suspected acute coronary ischemia. Methods: The present prospective observational study examined the prognostic significance of MPO in 917 patients with suspicion of acute coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Myeloperoxidase as a prognostic marker in ACS patients has generated conflicting results in clinical studies. The majority of clinical data has confirmed the prognostic value of MPO in predicting mortality [9, 2629], and our analysis confirmed this correlation to be highly significant. However, although there was strong correlation between MPO levels and other clinical events such as MACE and recurrent myocardial infarction, this association did not reach statistical significance in individual trials or our analysis [9, 30, 31].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Myeloperoxidase as a prognostic marker in ACS patients has generated conflicting results in clinical studies. The majority of clinical data has confirmed the prognostic value of MPO in predicting mortality [9, 2629], and our analysis confirmed this correlation to be highly significant. However, although there was strong correlation between MPO levels and other clinical events such as MACE and recurrent myocardial infarction, this association did not reach statistical significance in individual trials or our analysis [9, 30, 31].…”
Section: Discussionsupporting
confidence: 83%
“…In accordance with these findings, we found that the prognostic value of MPO was the highest among studies with high proportion of AMI patients [10, 27] compared to those with higher percentage of unstable angina subjects [29, 34]. Additionally, timing of sample collection could have played a role in the variable results since MPO level was significantly higher immediately after STEMI [26, 35]. Although studies adopted different MPO cutoff values, our analysis was primarily focused on the prognostic value of MPO rather than its absolute value since the included studies used different MPO assays.…”
Section: Discussionsupporting
confidence: 67%
“…Higher MPO predicted worse cardiac outcomes and lower ejection fraction [ 46 , 47 ], indicating higher long-term mortality [ 48 ]. Koch et al [ 49 ] presented that greater than 306.3 pmol/L of MPO measured 24 h after the onset of symptoms was an independent predictor of 6-month mortality and major adverse cardiac events in patients with suspected MI. Rudolph et al [ 45 ] showed that MPO was a predictive marker of increased risk of adverse events at 30 days and 6 months in patients admitted with ACS.…”
Section: Myeloperoxidase (Mpo)mentioning
confidence: 99%
“…19,21 Preclinical blood sample collections before the administration of heparin could be an option for generating valid data. 22 Different studies have reported diverse results for correlations between MPO concentrations determined in different types of samples. A good positive correlation was reported by Wendland et al 17 between MPO concentrations for heparin and serum samples (r ¼ 0.79), but no correlation was seen between EDTA and heparin samples (r ¼ 0.21).…”
Section: Discussionmentioning
confidence: 99%